GEJALA FONOLOGIS TUTURAN DALAM INTERAKSI ACARA E-TALK SHOW WITH BHS DI TV - Jannah, Rihlatul; Linarsih, Yanti (Universitas Madura, 2022)
This research is a descriptive study using a qualitative approach. The object of this research is the speech of the host and guest star on the E-Talk Show with BHS on TV. The method used is the documentation method. Documentation is used to collect data and then reviewed. The documentation used in this study is in the form of videos. The results showed that the phonological symptoms of speech in the interactions of E-Talk Show With BHS programs were: (1) anaptaxis, (2) contractions, (3) labialization. There are phonological symptoms of anaptaxis in the form of prosthesis, epenthesis and paragog. Prosthesis data found there are 2 data in the form of the addition of the sound [h] and [?]. The epenthesis data has 1 data, namely the addition of the sound [h]. The paragog data found amounted to 11 data, namely the addition of the sound [h] and [?]. The phonological symptoms of contraction found were the grinding of phonemes /ə/, /h/, /i/, /m/, /s/, /a/. The omission of the phoneme occurs due to the influence of the speaker's pronunciation speed. This happens to speed up or simplify the pronunciation. The amount of data found is 35 data. The omission of one phoneme is 29 data. The omission of two phonemes is 5 data. The omission of three phonemes is 1 data. The phonological symptoms of labialization found amounted to 21 data. The data includes sound changes [l]-[lʷ], [d]-[dʷ], [t]-[tʷ], [j]-[jʷ], [s]-[sʷ], [p]-[ pʷ], [d]-[dʷ], [m]-[mʷ], [k]-[kʷ], [g]-[gʷ], [n]-[nʷ]. This labialization usually occurs due to pressure or prolongation of the sound when it is pronounced.